Cooperation for the approach of popular libraries and Wikimedia in the management of cultural projects - Villarreal, Mario (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
The presentation develops the experience of training popular libraries in Argentina that develop cultural management projects with a territorial and community perspective in cooperation with the National University of Villa María. The novelty of the proposal lies in the use of Wikimedia tools that have, among other aspects, the promotion of free and open culture and the decolonization of Internet content. Argentine popular libraries respond to their environment, providing their communities with cultural and educational assets that they would not otherwise be able to access. In this sense, the use of technological tools and free digital platforms such as Wikimedia can be of great help for the development of cultural projects that preserve and disseminate local heritage, promote cultural education and encourage reading. To achieve these objectives, it is essential to have adequate project management that allows planning, executing and evaluating the different actions developed within the framework of cultural projects. This implies moving from isolated activities to institutional projects that involve the community and the context. This is why the training proposal that we carry out has a strong axis in the recognition of cultural makers of our communities. The presentation will develop the assumptions that support the initiative as well as the educational strategy and finally reflections will be made on the impacts and scope of training. We hope to contribute to collective reflections that have at their center the right to culture and the decolonization of content on the internet